Valor biológico de las proteínas del producto comercial Pediasure Plus utilizado en nutrición artificial enteral - Alfaro Beltran, Iris Melina (2015)
ABSTRACT In this research the biological value of proteins Pediasure plus commercial product , used in nutritional therapy, using the biological method of net protein utilization ( NPU ) , for it was used Rattus rattus var. norvegicus , of 33-57 days old and 50-60 g in weight. A group aproteic based diet and the other group the food under study was administered , the results were : digestibility 96.5 %, NPU 87.72 % and biological value of 90, 86 %. An analysis of the results it is concluded that every 100 g of Protein Pediasure plus commercial product , the body assimilates 91 g.